Studi Etnomatematika: Penentuan Tanggal Masyarakat Baduy dan Hubungannya dengan Konsep Aljabar - Nindi Eliza; Heni Pujiastuti (Jurnal Ilmiah Pendidikan Matematika Al Qalasadi, 2022)
Abstract Mathematics is a subject that is notoriously difficult at school, but most people are not aware that in their daily activities they have applied mathematics. Baduy people apply a calendar system that is used to calculate auspicious days, marry off children, travel, or build a house. This study aims to reveal the mathematical concepts used in the life of the Baduy people that can be used as learning materials for mathematics. To reveal this, the researchers used Ethnomathematical Studies. In this study, the approach or type of literature study was used. Sources of data obtained from books, literature, notes, and various reports. Data collection techniques using literature study. The results of the study indicate that there is a mathematical algebra concept in the calendar system of the Baduy community and both are related to each other.